2008
DOI: 10.1007/s00268-008-9820-5
|View full text |Cite
|
Sign up to set email alerts
|

Use of Locum Tenens Surgeons to Provide Surgical Care in Small Rural Hospitals

Abstract: Given the difficulty of recruiting surgeons to practice in rural America, it is critical to develop strategies to address this problem. Although using locum tenens surgeons may allow rural hospitals to offer surgical services, the quality of surgical care could be compromised. Other means for delivering surgical services at rural hospitals that cannot recruit or retain a surgeon should be explored to ensure that rural residents have access to high quality surgical care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
16
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 20 publications
0
16
0
Order By: Relevance
“…This may suggest that hospitals need higher flexibility in their capacity to deliver anesthesia services. Historically, this was a case even before the introduction of the ACA [2, 14]. The length of the assignment was quite long suggesting that locum tenens are not hired to cover holidays, but they fill a sustained period of higher demand.…”
Section: Discussionmentioning
confidence: 99%
“…This may suggest that hospitals need higher flexibility in their capacity to deliver anesthesia services. Historically, this was a case even before the introduction of the ACA [2, 14]. The length of the assignment was quite long suggesting that locum tenens are not hired to cover holidays, but they fill a sustained period of higher demand.…”
Section: Discussionmentioning
confidence: 99%
“…A potential explanation for this is the use of locum tenens surgeons who fill short-term service needs. A recent study found that locum tenens surgeons were hired in 15% of surveyed hospitals in small urban clusters of 2,500 to 9,999 people, small towns with high commuting to small urban clusters, small towns with low commuting, and isolated rural areas 15 . The proportion of Rural Urban Commuting Areas that meet this description is three times higher in Wisconsin, compared to Maine and South Carolina 14 .The use of locum tenens, the regionalization of healthcare across states 16,17 as well as the retirement of a large proportion of general surgeons 18,19 likely explain the proportions of surgeons with fewer than 10 procedures.…”
Section: Discussionmentioning
confidence: 99%
“…Today, we see a handful of pediatric surgeons practicing exclusively as a locum tenens-a financially viable practice alternative that is an increasingly popular option in general surgery [8]. Locum tenens general surgical coverage is common in rural hospitals where the surgical workforce shortage is analogous to the situation seen in pediatric surgical practices [10].…”
Section: Discussionmentioning
confidence: 99%